The impact of urinary stress incontinence in young and middle-age women practising recreational sports activity: an epidemiological study. Issue 14 (26th September 2008) - Salvatore, S; Serati, M; Laterza, R; Uccella, S; Torella, M; Bolis, P-F
Abstract : Objectives: To evaluate the prevalence of urinary stress incontinence (USI) in menstruating women practising recreational sports activity, to detect specific sports with a stronger association with urinary incontinence (UI) and to evaluate risk factors possibly related to this condition. Design: Epidemiological study. Setting: Non-competitive sports organisations in the province of Varese, Italy. Participants: 679 women of fertile age, practising recreational sports activity. Intervention: Anonymous questionnaire on UI. Main outcome measurements: The questionnaire included questions about patients' general characteristics, occurrence of UI in relation to sport or daily general activities, time of onset of this condition, frequency of leakage episodes, correlation of incontinence with types of movements or sports, subjective impression of being limited on such occasions and/or necessity to modify the type of sport. Results: UI was reported by 101 women (14.9%). Of these, 32 (31.7%) complained of UI only during sports activity, 48 (47.5%) only during daily life and 21 (20.8%) in both circumstances. Body mass index and parity were significantly associated with the risk of UI. Looking at the different sports activities, a higher rate of incontinence was found in women participating in basketball (16.6%), athletics (15%), and tennis or squash (11%). 10.4% of women abandoned their favourite sport, because of USI, and a further 20% limited the way they practised their favourite sport to reduce leakage episodes. Conclusions: Female UI affects a significant proportion of young women practising non-competitive sports activity; it can cause abandonment of the sport or limitation of its practice.